Faktor yang mempengaruhi kemandirian belajar dalam projek penguatan profil pelajar pancasila - Tri Sulistiarini; Sri Marmoah; Muhammad Ismail Sriyanto (Didaktika Dwija Indria, 2023)
Project to Strengthen Pancasila Student Profile (P5) is very important to improve the character of students, especially independent learning. The novelty of this research is that it focuses on the factors that influence learning independence in the Pancasila Student Profile Strengthening Project (P5). This research uses descriptive qualitative methods with a qualitative approach. Factors that affect the learning independence of students in class are divided into two, namely internal factors and external factors. Internal factors include the ability of students to get used to learning on their own after understanding the teacher's explanation, focusing on working on projects, and developing interests according to their wishes. Meanwhile, external factors include a supportive family environment, a supportive community environment, supportive teachers, and friends who influence all attitudes of students. Factors that influence learning independence in the Project to Strengthen Pancasila Student Profiles (P5) for class II B and V B SD N Kleco II are influenced by internal factors and external factors.